1997
DOI: 10.1021/bi970730s
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis of LYS(11−36), a Peptide Derived from the β-Sheet Region of T4 Lysozyme, in TFE and SDS

Abstract: The solution conformation of a peptide LYS(11-36), which corresponds to the beta-sheet region in T4 lysozyme, has been examined in aqueous solution, TFE, and SDS micelles by CD and 1H NMR spectroscopy. Secondary structure predictions suggest some beta-sheet and turn character in aqueous solution but predict a helical conformation in a more hydrophobic environment. The predictions were supported by the CD and NMR studies which showed the peptide to be relatively unstructured in aqueous solution, although there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
32
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 66 publications
8
32
1
Order By: Relevance
“…At intermediate TFE concentrations, the spectra indicate β-structure. These spectra are similar to those obtained by Najbar et al (1997) at pH 4.8 in 10-mM potassium phosphate buffer.…”
Section: Association Constant and Potential Of Mean Forcesupporting
confidence: 84%
See 2 more Smart Citations
“…At intermediate TFE concentrations, the spectra indicate β-structure. These spectra are similar to those obtained by Najbar et al (1997) at pH 4.8 in 10-mM potassium phosphate buffer.…”
Section: Association Constant and Potential Of Mean Forcesupporting
confidence: 84%
“…At intermediate TFE concentrations, the spectra indicate β-structure. These spectra are similar to those obtained by Najbar et al (1997) at pH 4.8 in 10-mM potassium phosphate buffer.Figure 5 also shows fits for the spectra using the reference data set of Brahms and Brahms (1980). Figure 6 shows the extent of secondary structure obtained from these fitted spectra.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…For example, extensive use of the fragment dissection approach has been made to determine nucleation sites for the folding of T4 lysozyme (34,35). In that case it was found that peptide fragments corresponding to helical regions in the intact protein generally had an intrinsic tendency to be helical in the isolated fragments, but this was not the case for β-sheet regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, several peptides, mostly exceeding 50 amino acid residues, have nonhelical structures such as the C-␥ phorbol-binding domain (193), sapecin (194), leucocin A (195), epidermal growth factor (25), and tritrpticin (196). Some peptides show dramatically different structures depending on the lipidlike environment used (197,198). Others, such as gramicidin (199), bacterioopsin (121), fd bacteriophage coat protein (200), melittin (96), M2 channel peptides (201), and a myristoylated ARF-1 peptide (202) show little or no structural change (12).…”
Section: Structure Generation and Analysismentioning
confidence: 99%